ANALISIS PENYAJIAN LAPORAN OPERASIONAL BERBASIS AKRUAL PADA SATUAN KERJA PERANGKAT DAERAH (SKPD) PROVINSI SULAWESI TENGAH - Umar, Musdalifah Dj. (Katalogis, 2018)
The aims of the study are: 1) to determine operational report presentation according to accrual-based of government accounting standards; 2) to determine and analyze understanding of apparatus on the relationship between operational report and other financial components and also implementation of accrual-based operational report in governmental working units in Central Sulawesi. The study applies qualitative method with phenomenological approach. Informants consist of people who are directly involved in the preparation of financial statements, especially operational reports. The results show that the presentation of operational reports is prepared to complement reporting and accounting cycle on accrul-based so that operational reports have predictive value; the information can be used to predict the income of operational report that will be received to fund government activities in the coming period. Lack of understanding of apparatus about the relation of operational statement with other components of financial report that are operational report, report of equity change and balance sheet in its presentation, and lack of human resources with accounting education have caused low comprehension on accrual-based operational report presentation.